2014
DOI: 10.1016/j.jjcc.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treadmill training on endothelial function and walking abilities in patients with peripheral arterial disease

Abstract: The 12-week treadmill training program prolonged the asymptomatic walking distance. The improvement in FMD indicates a systemic effect of the treadmill program on endothelial function. The supervised treadmill training provides an effective and safe treatment option in patients with PAD. The effects of unsupervised exercise during follow-up period after treadmill programs remain tentative and underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
1
36
0
5
Order By: Relevance
“…52 A recent study of patients undergoing a 12-week exercise training program demonstrated an improvement in flow-mediated dilation compared with baseline, suggesting that improvements in endothelial function may be one mechanism mediating reduced symptoms of claudication after exercise training. 53 In addition, in an animal model of chronic atherosclerosis that simulated some features of PAD, a pharmacological intervention that improved exercise-induced blood flow also improved the animals' functional status. 54 The impaired vasodilation in patients with PAD is likely a sequela of the obstruction, and improvement in physiological vasodilation with exercise offers a potential therapeutic target.…”
Section: Endothelial and Microcirculatory Dysfunctionmentioning
confidence: 99%
“…52 A recent study of patients undergoing a 12-week exercise training program demonstrated an improvement in flow-mediated dilation compared with baseline, suggesting that improvements in endothelial function may be one mechanism mediating reduced symptoms of claudication after exercise training. 53 In addition, in an animal model of chronic atherosclerosis that simulated some features of PAD, a pharmacological intervention that improved exercise-induced blood flow also improved the animals' functional status. 54 The impaired vasodilation in patients with PAD is likely a sequela of the obstruction, and improvement in physiological vasodilation with exercise offers a potential therapeutic target.…”
Section: Endothelial and Microcirculatory Dysfunctionmentioning
confidence: 99%
“…In this context, Januszek et al [64] showed that 12 weeks of supervised, intermittent treadmill walking until induce claudication, three times a week, prolonged the asymptomatic walking distance and improved brachial artery FMD in 43% after program. Another study that tested the hypothesis of potential effects of endothelial function in PAD patients that underwent to a supervised treadmill training program of 12 weeks found that brachial artery FMD values increased by 45% after program and the patients with better walking abilities at baseline derived greater clinical and metabolic benefits [65] .…”
Section: Exercise Arterial Function and Cardiac Rehabilitationmentioning
confidence: 99%
“…The coexistence of vascular dysfunction both in conduit arteries and microvasculature in patients with PolyVD must be recognized. The achievement of functional improvement in the already sclerotic conduit arteries might be difficult, but the microvascular endothelial dysfunction might be modifiable and treatable by potential medical therapies and life-style intervention [32]; exercise training improved endothelial function in patients with PAD [33]. An effective therapeutic strategy may involve the development of treatment to improve microvascular endothelial dysfunction, as assessed by RHI, in patients with higher risks of cardiovascular events.…”
Section: Variablementioning
confidence: 99%